2015
DOI: 10.1016/j.electacta.2015.10.122
|View full text |Cite
|
Sign up to set email alerts
|

AuPd/Fe3O4-based three-dimensional electrochemical system for efficiently catalytic degradation of 1-butyl-3-methylimidazolium hexafluorophosphate

Abstract: Keywords: three-dimensional system AuPd/Fe 3 O 4 ionic liquids kinetic study degradation mechanism A B S T R A C T Ionic liquids (ILs) have been reported to be toxic and harmful to aquatic and terrestrial organisms, thus it is imperative to remove the residual ILs in various effluents. In this work, a three-dimensional (3D) electrocatalytic system with synthesized AuPd/Fe 3 O 4 nanoparticles (NPs) as particle electrodes (PEs) was established for the degradation of typical 1-butyl-3-methylimidazolium ([BMIM]) b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…The Fenton process, the catalytic formation of hydroxyl and hydroperoxy radicals by the disproportionation of hydrogen peroxide, can be considered one of the most efficient means for the degradation of organic pollutants in wastewater streams at low to moderate concentrations . Numerous studies have investigated the efficacy of H 2 O 2 generated in situ over Pd−Fe based catalysts utilising a range of hydrogen sources such as formic acid, hydroxylamine and hydrazine . Indeed Underhill et al .…”
Section: Application Of H2o2 As An In Situ Oxidantmentioning
confidence: 99%
“…The Fenton process, the catalytic formation of hydroxyl and hydroperoxy radicals by the disproportionation of hydrogen peroxide, can be considered one of the most efficient means for the degradation of organic pollutants in wastewater streams at low to moderate concentrations . Numerous studies have investigated the efficacy of H 2 O 2 generated in situ over Pd−Fe based catalysts utilising a range of hydrogen sources such as formic acid, hydroxylamine and hydrazine . Indeed Underhill et al .…”
Section: Application Of H2o2 As An In Situ Oxidantmentioning
confidence: 99%
“…[89b] Recently, AuPd/Fe 3 O 4 nanoparticles have been used as particle electrodes (PEs) in the electrochemical degradationo fI Ls. [91] The developeds ystem shows promisingr esults for [bmim][PF 6 ], the complete degradation of which is observed within 90 min under optimized conditions. The main intermediates observed by GC-MS are the same as those observed by Zhou in the ZVI/ AC microelectrolysis system, that is, 1-butyl-3-methyl-2,4,5-trioxoimidazolidine in the first step, which affords 1-butyl-3methylurea as an intermediate metabolite, and finally N-butylformamide as the end product.…”
Section: Advanced Oxidation Processes (Aops): Chemical Photochemicalmentioning
confidence: 99%
“…Thus, modifying the noble metal such as Pd with iron to synthesize composite catalyst should be desirable. For instance, Qin et al [12] synthesized AuPd/Fe 3 O 4 nanoparticles as PEs, and their results showed that…”
Section: Introductionmentioning
confidence: 99%